Gelatin Based Skin Regenerative Template: Market Research and Product Analysis - Reddy, Arjun G (2009)
Skin regeneration and wound management in the Bio-Pharma industry has been an area with constant research and new product development. The range of products includes foams, sheets, sprays, powders, hydrocolloids and gels. Majority of these products that exist in the market are collagen based products. However, using collagen products is very expensive and could also have long term risks on patient’s health. Furthermore, they do not regenerate the skin to its original shape and texture and thus leave a scar post treatment.